2019
DOI: 10.1142/s0218539319500049
|View full text |Cite
|
Sign up to set email alerts
|

An Attribute np Control Chart for Monitoring Mean Life Using Multiple Deferred State Sampling Based on Truncated Life Tests

Abstract: In this paper, we design an attribute [Formula: see text] control chart for monitoring the mean life of the product where the lifetime follows the Pareto distribution of the second kind. The lifetime of the product is determined by time truncated life test and the multiple deferred state sampling is used to declare the status of the manufacturing process. Control limit coefficients and multiple deferred state sampling parameters such as sample size and number of successive subgroups required to declare the sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…However, in practice, this may be di cult because the form of distribution of the process is unknown or deviates from normality, and the testing process is time-consuming and requires more cost. Hence, designing a control chart for monitoring nonnormal process variables under the time truncated test is preferred to inspect the lifetime of the product because only a few random sample items are inspected for a specified time [10] and have attracted the attention of many researchers. Aslam and Jun [11] designed an attribute control chart for Weibull distribution under a truncated life test.…”
Section: Introductionmentioning
confidence: 99%
“…However, in practice, this may be di cult because the form of distribution of the process is unknown or deviates from normality, and the testing process is time-consuming and requires more cost. Hence, designing a control chart for monitoring nonnormal process variables under the time truncated test is preferred to inspect the lifetime of the product because only a few random sample items are inspected for a specified time [10] and have attracted the attention of many researchers. Aslam and Jun [11] designed an attribute control chart for Weibull distribution under a truncated life test.…”
Section: Introductionmentioning
confidence: 99%
“…Khan et al [13] developed a variable control chart based on Weibull distribution. Balamurali and Jeyadurga [14] recommended an attribute np CC for observing mean life by means of multiple deferred state sampling under TLT. Quinino et al [15] suggested a CC for monitoring the process of mean under scrutinizing attributes using control limits of the commonly X-bar chart.…”
Section: Introductionmentioning
confidence: 99%
“…Jeyadurga et al 24 constructed the 𝑛𝑝 CC using repetitive sampling using Pareto distribution of second kind. More work using TTLT can be seen in Rosaiah et al, 25 Balamurali and Jeyadurga, 26 Rao et al, 27 Aslam et al, 19 Kowsalya et al, 28 Tanveer et al, 29 Adeoti and Ogundipe, 30 Aslam et al, 31 Zaka et al, 32 Riffat and Azam (2021) and Zaka et al 32 The Power function distribution (PFD) developed by Dallas 33 is widely utilized in Engineering, health risk assessments and environmental because of its simplicity in expression and easy to fit for many processes. Over the complicated probability models Meniconi and Barry 34 presented PFD as a better to fit in many real life situations.…”
Section: Introductionmentioning
confidence: 99%